The Agrophysiological Response of Local Cultivars Soybeans Whio was Given Gibberellins and Phosphorus-Potassium Fertilizer - Jalil Silea; Rina Kerinci (JURNAL AGRIYAN: JURNAL AGROTEKNOLOGI UNIDAYAN, 2019)
The use of Growth Regulator has begun to be intensely developed in the agricultural world. However, the response of each type of plant to Growth Regulator is different. Moreover, the Growth Regulator are combined with inorganic fertilizers. In order to obtain the effectiveness of Growth Regulator for plants, a lot of research is needed to be conducted so that information on the accuracy of dosages of Growth Regulato can be obtained. The aim of this study was to determine the agrofisiological response of local varieties of soybean plants that were given gibberellins Growth Regulator combined with the administration of Phosphorus-Potassium fertilizer and to obtain the appropriate dosage of gibberellins Growth Regulator. This research was conducted in September - December 2018 in the Village of Liya Togo sub-district South Wangi - Wangi - Wakatobi Regency. The research applied a factorial randomized block design. The seeds used were local Wakatobi cultivar soybeans from farmers' gardens. The results showed that the use of gibberellins as Growth Regulator gave a real influence on the agrofisiological character of soybeans, namely leaf area, number of pods per plant, productivity. The interaction between gibberellins and Phosphorus-Potassium fertilizer has a significant effect on the number of pods formed and the productivity produced. There are variations in the dose of gibberellins (1-3 g.10 L water-1) in providing a good response to each parameter of soybean plant growth.